2017
DOI: 10.1177/0001839217708984
|View full text |Cite
|
Sign up to set email alerts
|

Brokerage as a Public Good: The Externalities of Network Hubs for Different Formal Roles in Creative Organizations

Abstract: Although much is known about how brokerage positions in social networks help individuals improve their own performance, we know little about the impact of brokers on those around them. Our study investigates brokerage as a public good. We focus on the positive and negative externalities of specific kinds of brokers: ''hubs,'' who act as the main interfaces between members of their own network community (''network neighbors'') and members of other communities. Because hubs access diverse knowledge and perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 62 publications
2
121
0
Order By: Relevance
“…In addition, Hubs' brokering activities also harmed producers' contributions to the success of TV shows through a secondary process: Even when hubs were not used on the focal creative project, the overlap in personnel and high interdependence between different production teams meant that the delays and conflicts they created on certain projects had a ripple effect on other creative projects in the same community. These findings by Clement et al (2018) illustrate the benefits of considering brokerage positions and brokering activities together, and highlight that the effects of brokering activities on the collaborative pursuit of creative projects are complex and depend in part on the nature of others' jobs.…”
Section: Helpful Brokersmentioning
confidence: 73%
See 3 more Smart Citations
“…In addition, Hubs' brokering activities also harmed producers' contributions to the success of TV shows through a secondary process: Even when hubs were not used on the focal creative project, the overlap in personnel and high interdependence between different production teams meant that the delays and conflicts they created on certain projects had a ripple effect on other creative projects in the same community. These findings by Clement et al (2018) illustrate the benefits of considering brokerage positions and brokering activities together, and highlight that the effects of brokering activities on the collaborative pursuit of creative projects are complex and depend in part on the nature of others' jobs.…”
Section: Helpful Brokersmentioning
confidence: 73%
“…They proposed further that the extent to which hubs' brokering activities create a public good (i.e., improving others' outcomes by contributing to creative projects' success) or a public liability (i.e., hurting others' outcomes by undermining creative projects' success) depends on the functional role of the hub's "neighbors." Clement et al (2018) found support for these hypotheses using archival data from the French TV game show production industry. Specifically, whereas hubs positively influenced creative directors' contributions to the success of TV shows, they negatively influenced producers' contributions to the success of TV shows (operationalized as viewership scores).…”
Section: Helpful Brokersmentioning
confidence: 84%
See 2 more Smart Citations
“…For example, ethnographic research with producers of country music in Nashville highlights producers' role in facilitating coordination and cooperation between performers, musicians, songwriters, personal managers, production studio staff (e.g., engineers), and labels (Lingo & O'Mahony, 2010). Additional evidence for the important role brokering processes play in establishing and maintaining collaborative relationships comes from field research on the production of TV game shows (Clement, Shipilov, & Galunic, 2017), innovations in the automotive industry , and interdisciplinary collaborations in academia (Kaplan, Milde, & Cowan, 2017). Following the COR framework, we label third parties who engage in brokering behaviors that transform neutral or non-existent ties into positive ties-that is, independence into positive interdependenceintermediaries.…”
Section: Intermediary Behaviorsmentioning
confidence: 99%